O-008 A New Generation of Flow Diverters for Endovascular Treatment of Intracranial Aneurysms - A Multicentre Preliminary Clinical and Angiographic Experience in 161 patients with 186 Aneurysms. (14th July 2013) - Wakhloo, A; Lylyk, P; Vries, J De; Biondi, A; Taschner, C; Hartmann, M; Szikora, I; Pierot, L; Sakai, N; Sourour, N; Rennie, I; Skalej, M; et al.
Abstract : Objectives: Validated through in vitro and in vivo experimental studies a new generation of flow diverters (Surpass™ FD) was evaluated for treatment of intracranial aneurysms (IA). We present our multicentre preliminary clinical and angiographic experience. Methods: To achieve the calculated flow disruption between the parent artery and aneurysm, needed for a saccular thrombosis, single FDs, tailored to local haemodynamics, were placed endovascularly in parent arteries and bridging the aneurysm. Implants measured 2.5-5.3mm in diameter with a length of10–80mm. Enrolled were patients harbouring a wide range of non-acutely ruptured large and giant wide-neck, fusiform and multiple small aneurysms, blister-type aneurysms and aneurysms associated with segmental artery disease. All patients were pretreated with dual antiplatelet for at least 72 hours before surgery and continued on both agents for at least 3 months after treatment. Clinical and angiographic follow-up were typically performed at 1–3, 6, and 12 months. Results: A total of 186 consecutive IA in 161 patients (mean age 57.1 years, range 28–82 years; 71% female) were treated at 23 centres. Fifty-three aneurysms were smaller than 5 mm, 64 were 5–9.9mm in diameter, 47 were10–20mm in diameter, and 22 were larger than 20mm (aneurysm diameter 10.4 ± 0.7mm, neck size 6.0 ± 0.5mm [mean ± SEM]). The aneurysms originated in 63.4% of the cases from the internal carotid artery; in 22% and 14.5% of the cases they were located in the anterior circulation distal to Circle of Willis and posterior circulation respectively. Technical success was achieved in 182 aneurysms (98%); incorrect FD placement with partial aneurysm coverage was observed in 5 aneurysms (2.7%). FDs were placed over 4 previously placed stents for coil embolisation; average number of devices used per aneurysm was 1.05. Permanent morbidity and mortality during the follow-up period of 8.7 months (range 1–24 months) including periprocedural complications were encountered in 5/134 (3.7%) and 2/134 (1.5%) of patients, respectively, within aneurysms of the anterior circulation; and 1/27 (3.7%) and 4/27 (14.8%) of patients, respectively, with posterior circulation aneurysm (one patient died from cancer, two patients died of pneumonia). Ninety-seven patients (60%) with 112 aneurysms were available for clinical and angiographic follow-up. Progressive thrombosis with complete occlusion was seen in 71% of aneurysms of the anterior circulation and 64% of aneurysms located distal to Circle of Willis and in 72% of aneurysms of the posterior circulation and included cases with improper device placement or FD covering previous stents. Occlusion in the range of range 95–100% was seen in 79%, 68% and 89% of aneurysms of the anterior circulation, aneurysms located distal to Circle of Willis and posterior circulation respectively. Conclusion: Preliminary data demonstrate high safety and effectiveness profile of a new generation of FD for a wide range of IA of the anterior and posterior circulation without the need for coiling. Durability and high rate of progressive occlusion observed requires long-term follow-up studies. Disclosures: A. Wakhloo: 2; C; Surpass Medical/Stryker. 4; C; Surpass Medical. 5; C; Surpass Medical. P. Lylyk: None. J. De Vries: 1; C; Surpass/Stryker. A. Biondi: 2; C; Surpass Medical/Stryker. C. Taschner: 2; C; Surpass Medical/Stryker. M. Hartmann: None. I. Szikora: None. L. Pierot: None. N. Sakai: None. N. Sourour: 2; C; Surpass Medical/Stryker. I. Rennie: None. M. Skalej: None. F. Mery: None. F. Turjman: None. P. Brouwer: None. E. Boccardi: None. M. Gounis: 2; C; Surpass Medical. T. Surpass User Group: None.